2006
DOI: 10.1007/s00223-006-0045-z
|View full text |Cite
|
Sign up to set email alerts
|

Additional Weight Bearing during Exercise and Estrogen in the Rat: The Effect on Bone Mass, Turnover, and Structure

Abstract: Mechanical loading and estrogen play important roles in bone homeostasis. The aim of this study was to evaluate the effects of mechanical loading on trabecular bone in the proximal femur of ovariectomized rats. We hypothesized that mechanical loading suppresses bone resorption and increases bone formation, which differs from the suppressive effects of estrogen on both resorption and formation. Furthermore, we expected to find changes in trabecular architecture elicited by the effects of mechanical loading and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 67 publications
4
36
1
Order By: Relevance
“…In rat models of osteoporosis, various types of exercises including treadmill (Simões et al 2008), jump (Umemura et al 2008), whole body vibration (Sehmisch et al 2009), swim (Hart et al 2001), tower climbing (Notomi et al 2003), and resistance (Tromp et al 2006) have been examined for the influences on bone loss and demonstrated to improve their status effectively. However, the subsequent molecular events of exercise-triggered decrease in bone loss remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In rat models of osteoporosis, various types of exercises including treadmill (Simões et al 2008), jump (Umemura et al 2008), whole body vibration (Sehmisch et al 2009), swim (Hart et al 2001), tower climbing (Notomi et al 2003), and resistance (Tromp et al 2006) have been examined for the influences on bone loss and demonstrated to improve their status effectively. However, the subsequent molecular events of exercise-triggered decrease in bone loss remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, mechanical load produced by backpack loads increased bone mineral content and bone mineral density by 27% and 11% respectively, comparing to control groups (Tromp et al 2006). The same conclusion was made in experiments dealing with astronauts in zero gravity conditions and in other similar studies (Vico et al 2000;Shackelford et al 2004).…”
Section: Microarchitecture Of Cancellous Bone Tissuementioning
confidence: 88%
“…The femur is heavily loaded bone in humans, especially in the metaphyseal region; consequently cancellous bone tissue is more developed in this region compared to rats, because cancellous bone conducts mechanical forces better than cortical bone and acts like an armature and load absorber. Variations in bone tissue structure are strongly influenced by different levels of sex hormones, but intense load could preserve bone tissue volume despite low level of sex hormones (Tromp et al 2006;Mavropoulos et al 2007). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations